LEARNING STYLES: PREFERENCE OF THE NURSING STUDENTS OF THE UNIVERSITY OF MAGALLANES, CHILE - Bravo Mancilla, Patricia Nicolle; Backes, Vânia Marli Schubert; Canever, Bruna Pedroso (My University, 2020)
ABSTRACT Objective: to identify the preference of the Nursing students of the University of Magallanes as regards learning styles. Method: a quantitative, descriptive and correlational study of the cross-sectional type was conducted with 186 students from first to fifth year of the undergraduate course, with an age range between 18 and 45 years old. The Honey-Alonso Questionnaire of Learning Styles was applied during the second semester of 2018. For data analysis, distribution of frequencies, descriptive statistics and correlations (Spearman) for the learning styles, using the SPSS v. 22.0. Results: the learning style of highest moderate preference of the Nursing students was the Reflexive one, with a mean value of 53.20%, according to class and to years of study, followed by the Theoretical, with 39%. No statistically significant correlations were found between the years of study and the learning styles (p>0.05); on the other hand, most of the surveyed students present one and two learning styles. Conclusion: knowing the learning styles will allow designing methodological strategies which are adequate for the students' learning styles, and which allow streamlining the learning process. The students object of this study are analytical and reflexive individuals, which very well matches the profile of the Nursing students when it comes to putting their Nursing chores into action.
Keywords: learning; higher education; nursing students; professional training; nursing